Design and development of a new wireless EMG electrode with high voltage impulse notification feedback. (17th July 2016) - Kobayashi, H.; Tatsukami, Y.
Abstract : This paper deals with the development of a new wireless EMG electrode 'VAMPIRE-BAT/WASPS' for man–machine interface that can not only stream up EMG signal in real-time, but also give electric stimulus feedback to human operator. The authors' unique idea is 'stimulus feedback nearby the actuation point'. Their statement is that human response may be faster if feedback is applied exactly on or nearby the point of actuation (i.e. muscle). Firstly, they introduce their new EMG electrode device and its technical details with performance test result. Then, they also show experiments and their results to verify effectiveness of the idea of stimulus feedback nearby the actuation point. Graphical Abstract: